Investigating the L2 Writing Strategies Used by Skillful English Students - Arifin, S. (Universitas Pendidikan Ganesha, 2020)
Several studies have been conducted to investigate the writing strategies used by skilled and less-skilled English writers, particularly in the EFL context but only a few have attempted to observe the strategies employed by skillful/proficient English students, predominantly in the Indonesian context. Therefore, the interest of this research was to discover the types of writing strategies applied by three skillful English students while writing in English (L2) and evaluate their substantial effects. The participants were three graduate students majoring in English Education. Moreover, the data obtained from Think-Aloud Protocols, semi-structured interviews, and written drafts were analyzed and evaluated and the results showed the writing process of the students varied. On the whole, the disparities presented a more understanding of students' writing process. It was also discovered that the three students applied similar strategies but the major inconsistency was in the manner with each was implemented.